2013
DOI: 10.4238/2013.february.8.3
|View full text |Cite
|
Sign up to set email alerts
|

Polymorphisms of the bovine growth differentiation factor 9 gene associated with superovulation performance in Chinese Holstein cows

Abstract: ABSTRACT. Growth differentiation factor 9 (GDF9) belongs to the transforming growth factor β superfamily and plays a critical role in ovarian follicular development and ovulation rate. We examined the bovine GDF9 gene polymorphism and analyzed its association with superovulation performance. Based on the sequence of the bovine GDF9 gene, six pairs of primers were designed to detect single nucleotide polymorphisms of two exons and intron 1 of GDF9 using polymerase chain reaction-single-strand conformation polym… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
13
0
1

Year Published

2013
2013
2020
2020

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 17 publications
(15 citation statements)
references
References 40 publications
1
13
0
1
Order By: Relevance
“…However, studies examining mutations in bovine GDF9 are relatively rare. Tang et al (2013) first detected the two SNPs A485TA and A625C in GDF9 and reported significant associations with superovulation traits. In the present study, these two SNPs were detected in Holstein bulls.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…However, studies examining mutations in bovine GDF9 are relatively rare. Tang et al (2013) first detected the two SNPs A485TA and A625C in GDF9 and reported significant associations with superovulation traits. In the present study, these two SNPs were detected in Holstein bulls.…”
Section: Discussionmentioning
confidence: 99%
“…We selected two single nucleotide polymorphisms (SNPs), A485TA and A625T (Tang et al, 2013), which are located in intron 1 of the bovine GDF9 gene, to evaluate their effects on the quality traits of sperm from 129 Holstein bulls. Primer sequences (F: 5'-AACAGAAGCC ACCTCTACAAC-3' and R: 5'-CTGGACAAGATGCTAACCTC-3') and reaction conditions for these two polymorphisms were selected according to a previous study (Tang et al, 2013).…”
Section: Pcr Conditions and Genotypingmentioning
confidence: 99%
See 1 more Smart Citation
“…The variables were considered repeated measures as each variable was measured in two to four successive treatments (Yang et al, 2012). Their effects on superovulation traits including TNO, NDE, NTE, and NUO were analyzed using the general linear model procedure and were compared using the Duncan multiple range test (SAS 8.1) (Tang et al, 2013). Only factors with significant effects (genotype, season, and age; P < 0.05) were fitted in the final statistical model:…”
Section: Discussionmentioning
confidence: 99%
“…Superovulation traits were significantly influenced by age and season (all P < 0.05) (see Tang et al, 2013). The INHβA genotype had no significant influence on superovulation traits in Chinese Holstein cows (P > 0.05).…”
Section: Influence Of Fixed Effects On Superovulation Traitsmentioning
confidence: 99%